Sustainable development as the subject of interest of librarianship organizations - Fedorowicz-Kruszewska, Małgorzata (Interdyscyplinarium nauk o mediach i kulturze, 2020)
The 1990s might be perceived as the beginning of a more intense interest in libraries with sustainable development, mainly in the environmental context. The American Library Association (ALA) has certainly contributed to it via setting up the Task Force on the Environment (TFOE) in 1989, which is part of the Social Responsibility Round Table (SRRT). Another meaningful step in promoting sustainable development in librarianship was made by the International Federation of Library Associations and Institutions (IFLA), which in 2002 adopted Statement on Libraries and Sustainable Development. In that document IFLA approved the commitment to sustainable development, ensured that library and information services promoted sustainable development by providing free access to information and appealed employees of the library and information services sector to respect and promote the principles of sustainable development. The aim of the article is to trace to the activities of library organizations in the field of promoting sustainable development in librarianship starting from those mention in the abstract and ending with contemporary activities.